Influences on User Engagement in Online Professional Learning: A Narrative Synthesis and Meta-Analysis. (August 2021) - Lee, Jane; Sanders, Taren; Antczak, Devan; Parker, Rhiannon; Noetel, Michael; Parker, Philip; Lonsdale, Chris
The internet has become the chosen medium for professional learning. Completing professional learning can improve work performance; however, many individuals who begin online courses do not complete them. It is not well understood which influences keep individuals engaged in online professional learning. We address these issues with a systematic review. Our review of 51 studies and 9, 583 participants includes a narrative synthesis and a meta-analysis that examined influences on user engagement in online professional learning. We found that course design and employers' provision of time to complete learning are key for engaging learners. Other important influences were learners' reasons for learning (e.g., intrinsic value and perceived usefulness), access to learning support, and opportunities for interaction during the learning experience.